Incorporating the patient voice and patient engagement in GOAL‐Hēm: Advancing patient‐centric hemophilia care. Issue 1 (7th February 2022) - Roberts, Jonathan C.; Recht, Michael; Gonzales, Sarah E.; Stanley, Justin; Denne, Michael; Caicedo, Jorge; Rockwood, Kenneth
Abstract: Background: Goal Attainment Scaling for Hemophilia (GOAL‐Hēm) is a novel, hemophilia‐specific, validated patient engagement tool and patient‐reported outcome instrument. Objective: We evaluated the degree to which the language of GOAL‐Hēm was patient‐centric and the content valuable and relevant for people with hemophilia (PWH) and/or their caregivers. Patients/Methods: Patients and caregivers participated in one of three investigations: an online survey, one‐on‐one patient interviews, or a focus group. The survey and interviews assessed the clarity and relevance of the GOAL‐Hēm menu items. Interviews were semistructured, audio recorded, and transcribed verbatim. Feedback from interviews was coded as "clear, " "unclear, " "remove, " or "add." The focus group explored participants' experience of GOAL‐Hēm and elicited recommendations for implementation. Quotations from focus group and interview transcripts were indexed and charted to emergent themes for analysis. Results: Participants comprised 19 adults with hemophilia and 19 caregivers of children with hemophilia (survey, n  = 20; interview, n  = 12; focus group, n  = 6). After their feedback, 32% (15/48) of goals were retained unchanged. Further feedback resulted in the removal of 45% (286/635) of the goal descriptors, and 30% (193/635) of the retained descriptors were modified. Three new (total = 38) goals and 42 descriptors (total = 368) were added to the menu. Thematic analysis indicated that participants were enthusiastic about patient‐centric language, empowered through the goal‐setting process, and recognized GOAL‐Hēm could measure clinically meaningful change. Conclusion: By listening closely to patients and caregivers, we refined GOAL‐Hēm to better capture the experiences of PWH, enhance content validity, and augment implementation strategies. Incorporating the patient voice is integral to developing patient‐centered outcome measures.